Manifestasi Trauma Kolektif dalam Narasi Sosial Masyarakat Lebanon : Suatu Sintesis Kualitatif 1975-2024 - M. Agung Rahmadi; Helsa Nasution; Luthfiah Mawar; Nurzahara Sihombing (Pusat Riset dan Inovasi Nasional, 2025)
This study examines the manifestations of collective trauma in the social narratives of the Lebanese community through a meta-synthesis of 47 primary studies (1975-2024). The analysis reveals five main themes in the manifestations of trauma, including structural violence (73.4%), disintegration of collective identity (68.2%), transformation of intergenerational narratives (62.8%), communal resilience (57.9%), and reconstruction of collective memory (52.3%). Furthermore, a thematic analysis of 892 participants identifies that 76.5% of respondents exhibit symptoms of transgenerational Post-Traumatic Stress Disorder (PTSD), with 64.3% reporting chronic anxiety related to sectarian conflict. Additionally, these findings confirm a significant correlation (r = 0.78, p < 0.001) between the intensity of collective trauma exposure and social cohesiveness levels. Thus, these results expand upon the research of Sim et al. (2018) regarding transgenerational trauma and Kimhi et al. (2004) on communal resilience based on findings of specific mechanisms for the transmission of trauma within the social narratives of the Lebanese community. Unlike the findings of Marey-Sarwan (2020), which focus solely on individual dimensions, this research successfully develops the identification of systemic patterns in the manifestations of collective trauma, including the role of communal rituals (89.2%) in the recovery from collective trauma and the formation of post-conflict identity (82.7%). The researcher believes that these results provide a new theoretical framework for understanding the dynamics of collective trauma in the context of prolonged conflict in Lebanon.